Stability evaluation of emulsion-based topical preparations: a valuable potential of dynamic-mechanical thermoanalysis (DMTA) test as a rapid rheological alternative to conventional freeze-thaw test - Cekić, Nebojša; Savić, Sanela; Savić, Snežana (Archives of Pharmacy, 2023)
The assessment of stability in emulsion-based topical preparations can be approached through real-time monitoring and/or accelerated methods, drawing predictions from pertinent stability-related physicochemical parameters. Ensuring the robustness and durability of topical products during storage, transport, and application necessitates thorough stability testing. However, due to the diversity of emulsion types and their intended use, there is no universal standard test, placing the liability on formulators/manufacturer to tailor appropriate assessments. Notably, topical emulsions, particularly cosmetic variants, often exhibit impressive stability with extended shelf lives. Nonetheless, evaluating their stability and decision-making remain challenging and time-consuming in industrial contexts. This underscores the demand for alternative testing protocols that expedite stability assessments and predict emulsion-based product stability accurately. This article comprehensively surveys literature, enriched with practical insights, exploring core mechanisms behind emulsion stability and prevention of instability. The discussion encompasses diverse approaches to stability assessment, revealing methodologies and parameters under examination during testing. Particular focus is placed on the dynamic-mechanical thermoanalysis (DMTA) method explored as a rapid, rheologically-based alternative to the conventional freeze-thaw test, emphasizing its usefulness for expediting the stability evaluation of emulsion-based topical preparations.
Keywords: topical emulsions; physical stability; accelerated stability test; rheological tests; shelf life